Problem legalizacji związków partnerskich osób tej samej płci w kampanii wyborczej 2011 roku - Tomczak, Łukasz (Political Preferences, 2012)
The article presents differences between the electorate and political parties programs in a political right point of view according to the principle of same-sex couples to certificate their relations. Parties of the left such as the Democratic Left Alliance (Sojusz Lewicy Demokratyc- znej) and Palikot's Movement (Ruch Palikota) tried to support the idea of the same-sex couple partnerships however they didn't try to make them equal with the ordinary marriages. The vot- ers of those parties where more often ready to accept the same-sex couple partnerships, nev- ertheless the right side pulls in the opposite electorate. Most of the Civic Platform (Platforma Obywatelska RP) voters didn't support the same-sex couples partnership idea, that kind of at- titude dominate the Law and Justice (Prawo i Sprawiedliwość) electorate too.Nowadays the aversion to the same-sex couples rights can be clearly seen among the whole society. During the 2011 campaign also clearly become the increase of support for the same-sex couples partnership over the previous year especially in political left wing of elector- ate. Social ratio to the main aspects of the article divines polish political parties as much as the most of the voters, creating a big line between the left and the right side of polish politics.